2015
DOI: 10.3109/10428194.2015.1014368
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dose escalation trial of the novel proteasome inhibitor carfilzomib in patients with relapsed chronic lymphocytic leukemia and small lymphocytic lymphoma

Abstract: The proteasome complex degrades proteins involved in a variety of cellular processes and is a powerful therapeutic target in several malignancies. Carfilzomib is a potent proteasome inhibitor which induces rapid CLL cell apoptosis in vitro. We conducted a phase I dose-escalation trial to determine safety and tolerability of carfilzomib in relapsed/refractory CLL or small lymphocytic lymphoma (SLL). Nineteen patients were treated with carfilzomib initially at 20 mg/m2, then escalated in 4 cohorts (27, 36, 45 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Recently, we showed that carfilzomib, a selective and irreversible proteasome inhibitor, is a potent cytotoxic agent in CLL samples isolated from patients treated with ibrutinib, a well-tolerated, orally bioavailable Bruton’s tyrosine kinase inhibitor (10). While our present manuscript was under preparation a phase I trial conducted in a group of 19 patients with relapsed/refractory CLL showed modest activity of carfilzomib (43). In this study, the patient population was high risk with very unfavorable clinical and prognostic factors (i.e., 84% had a Rai stage between 3 and 4, 85% were IgVH unmutated, 47% had del(17p), 21% had del(11q), 68% were refractory to fludarabine and 70% had complex karyotype), which probably contributed to the poor response observed with carfilzomib.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, we showed that carfilzomib, a selective and irreversible proteasome inhibitor, is a potent cytotoxic agent in CLL samples isolated from patients treated with ibrutinib, a well-tolerated, orally bioavailable Bruton’s tyrosine kinase inhibitor (10). While our present manuscript was under preparation a phase I trial conducted in a group of 19 patients with relapsed/refractory CLL showed modest activity of carfilzomib (43). In this study, the patient population was high risk with very unfavorable clinical and prognostic factors (i.e., 84% had a Rai stage between 3 and 4, 85% were IgVH unmutated, 47% had del(17p), 21% had del(11q), 68% were refractory to fludarabine and 70% had complex karyotype), which probably contributed to the poor response observed with carfilzomib.…”
Section: Discussionmentioning
confidence: 90%
“…However, our report could not illustrate a correlation between the cytotoxic effect of carfilzomib and del (11q), which is associated with loss of ATM and progressive disease, or del (17p) because only 13% and 10% of the patients, respectively, presented these unfavorable genetic abnormalities. Furthermore, the authors of the phase I trial with carfilzomib did not investigate the cytotoxic effect of carfilzomib ex vivo at baseline to assess any correlation between the carfilzomib-induced cytotoxic effects ex vivo versus in vivo (43). This is particularly relevant since here we used 30 CLL patient samples and showed high interpatient variability in response to the cytotoxic effect of carfilzomib.…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib and, only recently, also carfilzomib were initially used for the treatment of multiple myeloma but several prospective trials proved their efficacy in lymphoproliferative disorders too, especially in MCL [31]. Instead, many trials investigating the impact of carfilzomib are ongoing (e.g., NCT02187133, NCT01959698, NCT01926665) or about to be designed while published phase I data is only available for chronic lymphocytic leukemia [32].…”
Section: Other New Drugsmentioning
confidence: 98%
“…The proteasome inhibitor (PI) bortezomib has demonstrated activity in FL in combination with rituximab and bendamustine [12, 13], alone and in combination with rituximab in lymphoplasmacytic lymphoma / Waldenstrom's macroglobulinemia LPL/WM [14, 15], and is FDA approved for use in relapsed MCL. Investigations of other PIs including carfilzomib and ixazomib are underway to identify active agents in the class with less neurotoxicity and improved ease of administration [16, 17]. …”
Section: Targeted Therapies For Ib-nhlmentioning
confidence: 99%